Preliminary Design and Computational Fluid Dynamics (CFD) Analysis of Liquid Fluid Flow Through a Split Cylindrical Object - Baananto, Fauzan (IRA Jurnal Teknik Mesin dan Aplikasinya (IRAJTMA), 2023)
Computational Fluid Dynamics is a method for solving engineering problems, especially in cases of fluid flow, heat transfer and various related fluid phenomena such as chemical reactions. This CFD research aims as preliminary design to determine the effect of fluid flow passing through a split cylindrical object. There are three main elements in CFD programming to solve the problem of fluid flow through a split cylindrical object, (1) Pre-processor (2) Solver and (3) Post-processor which is the procedure used in this research. The flow value on the inlet side is 0.0001 m/s or in conditions Re ≤ 5 or in laminar flow conditions. The fluid used in this research is water with a density of 1.2 kg/m3. Then the resulting grid system or meshing is 21535 nodes and 21194 elements. The conclusion of this research is that the flow vortex that occurs in a split cylindrical object is smaller when compared to a cylindrical object, but the flow vortex that occurs is still larger when compared to a square object.